An Analysis of the Principles of Human Rights in Islam - Abdulraheem, Nimah Modupe (NIU Journal of Humanities, 2017)
The concept of human rights in Islam presupposes that the purpose of existence under Islamic law is basically to serve Allah. Hence the duty of man towards his creator embraces both his duty to the society and to his fellow human beings. The relationship between the concept of human rights in Islam and that of the West has been a very controversial one. It is the belief of the West that non-Western cultures, including Islam did not possess the notion of human right before it was conceptualized by them. While not denying the fact that contemporary human rights law are basically products of Western civilization, this paper argues that human right is not an exclusive idea of the West as the idea was first conceived in Islam some fourteen centuries ago and that the principles which were enshrined in the contemporary human right instruments were originally conceptualized by Islam from its cradle. This paper therefore analyses the principles of human rights in Islam with a view to ascertaining its existence in Islamic culture before the Western conception. The paper intends to argue further that since Islam predates the Western notion of human rights, it then means that genuine human rights are contained in Islam.  It will at the end concludes that Islam is a complete way of life and has left no stone unturned, including the concept of human rights.